Is Dyssynergic Defecation an Unrecognized Cause of Chronic Constipation in Patients Using Opioids?. (November 2019) - Nojkov, Borko; Baker, Jason; Menees, Stacy; Watts, Lydia; Collins, Kristen; Armstrong, Moira; Thibault, Mackenzie; Harer, Kimberly; Lee, Allen; Eswaran, Shanti; Saad, Richard; Chey, William D.
Abstract : OBJECTIVES: The impact of opioids on anorectal function is poorly understood but potentially relevant to the pathogenesis of opioid-induced constipation (OIC). To evaluate anorectal function testing (AFT) characteristics, symptom burden, and quality of life in chronically constipated patients prescribed an opioid (OIC) in comparison with constipated patients who are not on an opioid (NOIC). METHODS: Retrospective analysis of prospectively collected data on 3, 452 (OIC = 588 and NOIC = 2, 864) chronically constipated patients (Rome 3) who completed AFT. AFT variables included anal sphincter pressure and response during simulated defecation, balloon expulsion test (BET), and rectal sensation. Dyssynergic defecation (DD) was defined as an inability to relax the anal sphincter during simulated defecation and an abnormal BET. Patients completed Patient Assessment of Constipation Symptoms (PAC-SYM) and Patient Assessment of Constipation Quality of Life (PAC-QOL) questionnaires. RESULTS: The mean age of the study cohort was 49 years. Most patients were women (82%) and whites (83%). Patients with OIC were older than NOIC patients (50.7 vs 48.3, P = 0.001). OIC patients were significantly more likely to have DD (28.6% vs 21.4%, P < 0.001), an abnormal simulated defecation response on anorectal manometry (59% vs 43.8%, P < 0.001), and an abnormal BET (48% vs 42.5%, P = 0.02) than NOIC patients. OIC patients reported more severe constipation symptoms ( P < 0.02) and worse quality of life ( P < 0.05) than NOIC patients. DISCUSSION: Chronically constipated patients who use opioids are more likely to have DD and more severe constipation symptoms than NOIC.